Domestic Politics and External Financial Liberalization in China: The Capacity and Fragility of External Market Pressure. Issue 108 (2nd November 2017) - Lombardi, Domenico; Malkin, Anton
Abstract: This article explores how the Chinese Communist Party has relied in part on making global financial markets and institutions a source of external pressure to help pass domestic economic and financial reform. We explore two case studies of external financial liberalization: the listing of Chinese state-owned enterprises on foreign stock exchanges and the financial reform aspects of the Shanghai Free Trade Zone. These studies show that external liberalization policies are interlinked with both micro- and macro-level reforms in the domestic economy. We conclude that, after 2005, this strategy of applying external pressure, in fact, did not lead to more comprehensive economic restructuring because the agents of external pressure—in this instance, foreign banks and accounting firms—were themselves party to the reinforcement of state control and ultimately did not (or could not) promote further external liberalization. Domestic agents that supported external liberalization were also quick to abandon it when external pressure conflicted with other domestic policy objectives.